2021
DOI: 10.1177/02692155211032655
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the implementation of a Communication Enhanced Environment model on an acute/slow stream rehabilitation and a rehabilitation ward: A before-and-after pilot study

Abstract: Objectives: Develop and implement a Communication Enhanced Environment model and explore its effect on language activities for patients early after stroke. Method and design: Before-and-after pilot study. Setting: An acute/slow stream rehabilitation and a rehabilitation ward in a private hospital in Perth, Western Australia. Participants: Fourteen patients recruited within 21 days of stroke. Seven recruited during the before-phase (control group: patients with aphasia = 3, patients without aphasia = 4) and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…With the majority of stroke survivors returning home after their hospital admission (Stroke Foundation, 2020), it is critical to optimize communication so that PWA and their loved ones experience frequent, enjoyable and significant conversations. Successful communication is likely to foster improved language function by establishing an enriched communication environment (D'Souza et al., 2022) that enhances neuroplasticity (Hannan & Nithianantharajah, 2006), enabling family caregivers to maintain their carer role in the long‐term and support the person with aphasia's community participation.…”
Section: Introductionmentioning
confidence: 99%
“…With the majority of stroke survivors returning home after their hospital admission (Stroke Foundation, 2020), it is critical to optimize communication so that PWA and their loved ones experience frequent, enjoyable and significant conversations. Successful communication is likely to foster improved language function by establishing an enriched communication environment (D'Souza et al., 2022) that enhances neuroplasticity (Hannan & Nithianantharajah, 2006), enabling family caregivers to maintain their carer role in the long‐term and support the person with aphasia's community participation.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, participants described entertainment options (eg, television programming/system navigation required complex language) as unsuitable or overstimulating and suggested simple music options or available (and quiet) green spaces. Recent studies in Australia and the UK have explored the feasibility of enriching hospital environments 59 and alternative ways to improve well-being for PWA. 60 …”
Section: Discussionmentioning
confidence: 99%
“… 18 The broad nature of the facilitative environment is illustrated by the essential features of stroke unit care: 69 , 70 Structured assessment procedures Policies on early stages of management of common problems Policy on the ongoing rehabilitation Expertise in stroke management and rehabilitation with regular team education Multidisciplinary teamwork with regular planned team meetings Involvement of patients and families Other studies have shown that: Planned changes in the physical environment alter the behaviour of patients, increasing their activities. 71 74 Social factors influence adaptation; for example, after a stroke, community activity is influenced by social networks 75 and being with other people is associated with more movement of the affected arm. 76 The harm caused by inappropriate environments is also clear.…”
Section: Discussionmentioning
confidence: 99%
“…Planned changes in the physical environment alter the behaviour of patients, increasing their activities. 71 74 …”
Section: Discussionmentioning
confidence: 99%